Ultralow Ru Loading Transition Metal Phosphides as High‐Efficient Bifunctional Electrocatalyst for a Solar‐to‐Hydrogen Generation System. Issue 28 (5th June 2020) - Chen, Ding; Pu, Zonghua; Lu, Ruihu; Ji, Pengxia; Wang, Pengyan; Zhu, Jiawei; Lin, Can; Li, Hai‐Wen; Zhou, Xiangang; Hu, Zhiyi; Xia, Fanjie; Wu, Jingsong; et al.
Abstract: Water splitting is a promising technology for sustainable conversion of hydrogen energy. The rational design of oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) bifunctional electrocatalysts with superior activity and stability in the same electrolyte is the key to promoting their large‐scale applications. Herein, an ultralow Ru (1.08 wt%) transition metal phosphide on nickel foam (Ru–MnFeP/NF) derived from Prussian blue analogue, that effectively drivies both the OER and the HER in 1 m KOH, is reported. To reach 20 mA cm −2 for OER and 10 mA cm −2 for HER, the Ru–MnFeP/NF electrode only requires overpotentials of 191 and 35 mV, respectively. Such high electrocatalytic activity exceeds most transition metal phosphides for the OER and the HER, and even reaches Pt‐like HER electrocatalytic levels. Accordingly, it significantly accelerates full water splitting at 10 mA cm −2 with 1.470 V, which outperforms that of the integrated RuO2 and Pt/C couple electrode (1.560 V). In addition, the extremely long operational stability (50 h) and the successful demonstration of a solar‐to‐hydrogen generation system through full water splitting provide more flexibility for large‐scale applications of Ru–MnFeP/NF catalysts. Abstract : Ru–MnFeP/NF, with a unique nanosheet structure, is synthesized by Ru loading and subsequent phosphation, derived from a metal–organic framework. The material exhibits both superior oxygen evolution reaction and hydrogen evolution reaction activities and stabilities in alkaline media.